Kepercayaan Kejawen Islam dalam Perspektif Agama Islam - Lala Gita Zahra Muslim; Nahla Malika Hamdani; Dian Pratiwi Puspitasari; Sasikirani, Andien (Moderasi: Jurnal Kajian Islam Kontemporer, 2023)
Kejawen is a tradition that exists in Indonesia, Kejawen itself comes from the Java region in the form of beliefs and traditions, these beliefs are passed down from generation to generation, Kejawen is not recognized as a religion in Indonesia. This belief is shared by all religions, so people who believe in Javanese also have their own religion. This journal will present Islamic Javanese from the perspective of Muslims, whether Islamic Javanese is considered Musryik or not, how Islamic religious leaders respond to Javanese beliefs, whether this belief is allowed in the Islamic religion